Study of Fabricated Solar Dryer of Tomato Slices under Jordan Climate Condition - Olimat, Abdullah Nasrallah (International Journal of Renewable Energy Development, 2017)
The objective of the current study was to investigate experimentally, the performance of a fabricated solar dryer under Jordan climate condition during the summer of 2013. The temporal variations of temperature difference between absorber plate and ambient temperature were obtained in the results and its influence on the performance of solar flat plate collector was examined. The effects of absorber plate temperature, ambient temperature and wind heat transfer coefficient on the top heat loss coefficient were also investigated. The results showed that the efficiency of the collector ranging between 45 to 66 % which affected significantly by the amount of solar irradiation during the day. Only top heat loss was taken into considerations, since other losses were very small and might be negligible. Also the results confirmed that the performance of collector was maximum when the difference between plate and ambient temperatures was maximum. In addition, this work presented an indirect forced convection solar dryer, which consists of solar heater, fan and drying chamber. Fan was used to force the heated air through chamber to increase the drying rate. Â A 500 gram of tomatoes were dried to the final moisture content 28% from 95% (w.b). The experimental moisture ratios of the tomatoes were fitted to four mathematical drying models. Comparisons between these modes are sought using statistical analysis in the results. The fit quality obtained with each model was evaluated. After the comparison with the experimental obtained values, it was concluded that polynomial equation with second order represents the drying characteristics better than the other models by indicating high value of coefficient correlation (R2= 0.999564 ) and low values of other parameters( ðžŒ2= 0.000203; RMSE= 0.01011; MBE= 0.000102 ) compare with other models. The effective moisture diffusivity was estimated using Fick's second law and was Â m2/s with an average temperature of 306 K.Article History: Received January 14th 2017; Received in revised form April 28th 2017; Accepted June 10th 2017; Available onlineHow to Cite This Article: Olimat, A.N. (2017) Study of Fabricated Solar Dryer of Tomato Slices Under Jordan Climate Condition. International Journal of Renewable Energy Development, 6(2), 93-101.https://doi.org/10.14710/ijred.6.2.93-101